1975
DOI: 10.1172/jci108236
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid levels in maternal and cord serum after prenatal betamethasone therapy to prevent respiratory distress syndrome.

Abstract: A B S T R A C T Serumii glucocorticoid levels were (letermined in 20 inothers andI 43 premature infalnts wh-lio r-eceived prenatal betamnetlhasonie therapy for preventionl of respiratory distress syndrome (RDS). 'Maternal betamethasone peaked at 75 ,ug cortisol equivalents per 100 ml 1 h after injection of 12 mg steroid and declined to half by 6 h. Betamethasone in cord blood w-as 14.3 tig cortisol equivalents per 100 ml at 1 h, decreased to a level of 4.7 at 20 h, aand was not detected 2 days after a second d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0
10

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(109 citation statements)
references
References 30 publications
8
91
0
10
Order By: Relevance
“…These results may be due to differences in the animal species used, the order of and interval between exposure to antenatal steroids and initiation of intrauterine inflammation, or the continuity of inflammatory stimuli by live bacteria or a single LPS injection. In the current study, the anti-inflammatory action of betamethasone might have persisted despite continuous inflammatory stimuli by live bacteria in utero before delivery, in accordance with the human study (28) showing that peak fetal serum betamethasone levels measured 1-2 h after maternal betamethasone treatment returned to baseline within 2 d of treatment.…”
Section: Chorioamnionitis and Steroid For Bpdsupporting
confidence: 90%
“…These results may be due to differences in the animal species used, the order of and interval between exposure to antenatal steroids and initiation of intrauterine inflammation, or the continuity of inflammatory stimuli by live bacteria or a single LPS injection. In the current study, the anti-inflammatory action of betamethasone might have persisted despite continuous inflammatory stimuli by live bacteria in utero before delivery, in accordance with the human study (28) showing that peak fetal serum betamethasone levels measured 1-2 h after maternal betamethasone treatment returned to baseline within 2 d of treatment.…”
Section: Chorioamnionitis and Steroid For Bpdsupporting
confidence: 90%
“…(and i.v. ) Maltau et al (1979) and Ballard et al (1975) found, as we did, that maternal cortisol levels fell to about 10-30% of predose levels in the 24 h after the first 12 mg dose of the suspension, and began to increase again 2-4 days after the last dose had been given. The number of doses used in these studies varied from one dose to three doses given 24 h apart.…”
Section: Discussionsupporting
confidence: 78%
“…Some work has been done by Tsuei et al (1980) who examined the disposition and placental transfer of dexamethasone in pregnant women approaching delivery. Also, Ballard et al (1975) measured betamethasone and cortisol levels in pregnant women after a 12 mg dose of betamethasone as a 'sustained release' formulation. In that study, cortisol levels were measured using a CBG-isotope assay and total glucocorticoid levels using a radioreceptor assay; the difference was attributed to betamethasone.…”
Section: Introductionmentioning
confidence: 99%
“…However, as synthetic fluorinated steroids are not inactivated by 11βHSD2, placental permeability is high and there is a possibility that the fetus is exposed to synthetic GC from the mother. Permeability is reported to be 100% for dexamethasone and 30-50% for betamethasone [56]. Thus, the use of HC or prednisolone [48,57] is highly recommended during pregnancy.…”
Section: [Pregnancy]mentioning
confidence: 99%